Distinguishing the mechanisms driving multifaceted plant diversity in subtropical reservoir riparian zones - Zheng, Jie; Arif, Muhammad; He, Xinrui; Liu, Xiaolin; Li, Changxiao (Frontiers in Plant Science, 2023)
Dam-induced water level fluctuations dramatically alter various aspects of riparian diversity, such as taxonomic (TD), phylogenetic (PD), or functional (FD) diversity. Understanding the multifaceted plant diversity and its maintenance mechanisms is crucial for conserving riparian biodiversity. However, most studies have focused only on TD, and less is known about PD and FD. Here we integrated TD, PD, and FD diversity along inundation gradients of 30 m elevation in a 58,000 km2 landscape within the Three Gorges Reservoir Region, China. This research aims to assess how distinct ecological processes affect the plant community assembly and how they respond to inundation gradients, spatial variability, climate, and soils in dam-regulated riparian zones. We found that alpha TD, PD, and FD diversity exhibited decreasing trends with increasing inundation gradients and significant positive correlations with soil organic matter. The number of clustering plant communities increases along the inundation gradients. Beta TD and PD diversity were mainly dominated by species turnover with fewer contributions from nestedness, while functional diversity was mainly dominated by nestedness with fewer contributions from species turnover. The explainable rates of different dimensions of beta diversity, turnover, and nestedness ranged from 11% to 61%, with spatial factors explaining the highest beta diversity in different dimensions, followed by inundation gradients, soil properties, and climate variables. Our results suggest dispersal limitations are more important for species turnover in dam-regulated riparian zones at larger scales, while inundation gradients and soil fertility are more critical in shaping plant community assemblages at the local scale. This study emphasizes that environmental and spatial gradients are critical for understanding the assembly mechanisms driving multifaceted plant communities at multiple scales, and reinforces the importance of incorporating multiple biodiversity dimensions for biodiversity conservation in subtropical reservoir riparian zones.